Web-based system for creative writing - Rizki Zulfikar; Annisa Sari Putri (Politeknik Negeri Bali, 2020)
Due to the rapid technological development, online business is at a high peak and yet to attract people to buy things on the internet is not as easy as it sounds. The purpose of this study is to describe the importance of the role of creative writing in online marketing. The method used for this study is secondary data, where all the sources are obtained from previous research, including collecting data from articles, books, or online websites. The results indicate that creative writing is one of the most important elements to promote a product or a service for business over the internet. Most people nowadays prefer to buy things online because it is indeed an easier and simpler way. However, to promote and attract more people to look at our online products is not as easy as it sounds. It is because we cannot taste, smell, touch, and feel things while doing online shopping. That is why we need creative writing in order to create a strong visual in the reader’s mind.